2008
DOI: 10.1007/bf03016089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activated protein C on the mesenteric microcirculation and cytokine release during experimental endotoxemia

Abstract: Purpose: Activated protein C (APC) is the first anti-inflammatory drug to be approved for the treatment of severe sepsis. However, the underlying mechanisms are not completely elucidated. Therefore, the aim of our study was to evaluate the effects of APC on the microcirculation (mesenteric leukocyteendothelial interaction, plasma extravasation) using intravital microscopy (IVM) and on cytokine release during experimental endotoxemia in rats. Methods: We divided forty, male, Lewis rats into four groups (n = 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…As the accumulation of pro-inflammatory cytokines could lead to inflammatory cascades and results in organ failure and mortality, many of them have been chosen as therapeutic targets for endotoxemia. It was reported that activated protein C decreased the deterioration of the mesenteric microcirculation and endotoxin-induced TNF-a production 8 . Since TNF-a is thought to be one early released inflammatory cytokines, which would reach to peak within 1.5-2 h after the administration of LPS 2 , and thus suppressing the level of TNF-a could attenuate the overwhelming inflammation responses in endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the accumulation of pro-inflammatory cytokines could lead to inflammatory cascades and results in organ failure and mortality, many of them have been chosen as therapeutic targets for endotoxemia. It was reported that activated protein C decreased the deterioration of the mesenteric microcirculation and endotoxin-induced TNF-a production 8 . Since TNF-a is thought to be one early released inflammatory cytokines, which would reach to peak within 1.5-2 h after the administration of LPS 2 , and thus suppressing the level of TNF-a could attenuate the overwhelming inflammation responses in endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a is one of the most important early releasing cytokines in endotoxemia, and it was reported that the accumulation of TNF-a would lead to the secondary inflammatory cascades, such as up-regulation of cell adhesion molecule and reactive oxygen species 7,8 . Numbers of treatments of endotoxemia studies showed protective effect by suppressing TNF-a level [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aminosteroids), anti-inflammatory drugs and anticoagulants. (20,(24)(25)(26) Also, several antibiotics which possess vasoactive and anti-inflammatory properties may ameliorate decrements in microcirculation function. (27) Another approach is the use of different crystalloid and/ or colloid fluids.…”
Section: Therapeutic Approaches To Improve the Microcirculation In Sementioning
confidence: 99%
“…We have previously reported that aPC modulates the hepatic inflammatory response, at least in part, via a leukocyte-dependent mechanism (14). Furthermore, treatment with aPC attenuates mesenteric microcirculatory failure induced by endotoxin challenge (15). Despite these findings, the precise mechanism(s) by which aPC modulates hepatic endothelial dysfunction remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 96%